Expressive Language Development of Children with Speech Delay in Early Childhood Education Environments - Adies Ganistya Nabila; Eny Nur Aisyah; Wuri Astuti (Jurnal CARE (Children Advisory Research and Education), 2026)
Expressive language ability can be defined as a child’s capacity to articulate words and use language to convey their thoughts to others. This study aims to describe and identify the expressive language development of early childhood learners who experience speech delay, as well as to examine the factors that influence this development within the context of early childhood education environments. The research employs a descriptive qualitative approach using a case study method. Data were collected through triangulation, drawing from observations, interviews, and documentation. The data analysis followed the Miles and Huberman model, which includes data collection, data display, data condensation, and conclusions drawing/verifying. The findings indicate that the expressive language development of children with speech delay is not solely dependent on the child’s internal conditions, but is also influenced by support from the educational environment. Effective collaboration between teachers and parents serves as a key factor in successfully enhancing the expressive language abilities of children with speech delay.